Synthesis of Thiazolidine Derivatives from Schiff bases and study their as Antibacterial Effect - Noor Abdulhassan Alsaady; Nahid Sabah aldin Saber; Anfal Abdulhassan Alsaady (Journal of Biomedicine and Biochemistry, 2025)
This research includes the synthesis of some new heterocyclic derivatives (pyridine derivatives), firstly reaction of (2-amino-5-chloropyridine, 2-amino-4- methyl pyridine) With aromatics benzaldehydes (p-bromobenzaldehyde, dimethyl amino benzaldehyde , p-chlorobenzaldehyde, Salicylic aldehyde, p- amino benzaldehyde) to form different derivatives of schiff bases, secondly reaction of Schiff base derivatives with thioglycolic acid to form thiazolidinone derivatives, all resulting compounds characterized by FT-IR.